IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH - Miftahul Huda; Mohammad Erihadiana (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2021)
This study tries to analyze the implementation of Human Resources (HR) management in MTs. Manbaul Huda Bandung City in improving the quality of education. This study uses qualitative methods, namely research procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The result of this research is that the implementation of human resource management in MTs. Manba'ul Huda Kota Bandung, among others: 1) Employee planning, 2) Employee procurement, 3) Employee guidance and development, 3) Promotion and transfer, 4) Employee dismissal, 5) Compensation and rewards. Related to efforts to improve the quality of education of school principals, the provision of awards in the form of free Umrah rewards and punishments in the form of transfer of positions or layoffs, the provision of rewards and punishments has a considerable influence on the work motivation of educators and educational staff so that it can improve the quality of education in these madrasas. The suggestions from the results of this study include: first, a strong figure of the head of the madrasah so that it is always maintained. Second, giving rewards and punishments in motivating the performance of educators and education personnel, is expected to continue to be carried out and even increase both in material and non-material characteristics.